A Trend Analysis of Growth and Development of Micro, Small and Medium Enterprises (MSMEs) in India - Dr. H M Naveen (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The Micro, Small and Medium Enterprises (MSMEs) review the policies and programmes and make suitable recommendations regarding the promotion and development of products and services to meet the demands of the domestic as well as global marketing. The ministry of MSMEs sector organizes and implements various schemes focusing on financial assistance, technological assistance as well as upgradation, infrastructure development, skill development and training, enhancing market assistance of MSMEs. An overview of the MSMEs Sector, the organizational structure of the Ministry of MSMEs., role of the office of Development commissioner, setting up of National Board for MSMEs as well as recent developments in MSMEs – are depicted in this article.
Keywords: MSMEs; Organizational Structure; Development Commissioner; National Board-MSMEs; Recent Developments